Respuesta :

Answer:

1. Set A

2.  [tex]\textsf{Apply\:Difference\:of\:Two\:Squares\:Formula:\:}\left(a+b\right)\left(a-b\right)=a^2-b^2[/tex]

3.

[tex](x+7)(x-7)[/tex]

[tex]\implies a=x\:\textsf{and}\:b=7[/tex]

[tex]\implies x^2-7^2=x^2-49[/tex]

[tex](x-9)(x+9)=(x+9)(x-9)[/tex]

[tex]\implies a=x\:\textsf{and}\:b=9[/tex]

[tex]\implies x^2-9^2=x^2-81[/tex]

[tex](4x-3)(4x+3)=(4x+3)(4x-3)[/tex]

[tex]\implies a=4x\:\textsf{and}\:b=3[/tex]

[tex]\implies (4x)^2-3^2=16x^2-9[/tex]

4.

[tex](2x+5)(2x-5)[/tex]

[tex]\implies a=2x\:\textsf{and}\:b=5[/tex]

[tex]\implies (2x)^2-5^2=4x^2-25[/tex]

5. [tex](x-6)(x-6)[/tex]

Cannot use Difference of Two Squares Formula to expand this expression.  To expand this expression, you would need to use the FOIL method: [tex]\left(a+b\right)\left(c+d\right)=ac+ad+bc+bd[/tex]

[tex]\implies (x-6)(x-6)=x^2-6x-6x+(-6)^2=x^2-12x+36[/tex]

Answer:

1.Set A

2.Aplyyanses of shortcut based

[tex] \beta \sin( \sec( \cos(e \alpha \% log_{14 |kkjja| }(?) ) ) ) bcaue \: f \: thd \: \: aakdx[/tex]

Step-by-step explanation:

thire9